2005
DOI: 10.1007/s00246-004-0919-7
|View full text |Cite
|
Sign up to set email alerts
|

Successful Use of Recombinant Factor VIIa (NovoSeven) During Cardiac Surgery in a Pediatric Patient with Glanzmann Thrombasthenia

Abstract: Glanzmann thrombasthenia is a rare, hereditary, congenital disorder of platelet function characterized by inappropriate bleeding that is difficult to control. Recombinant activated factor VII (rFVIIa) is a new treatment that is used to stop bleeding and provide surgical support for these patients. This report describes the use of rFVIIa to prevent serious bleeding during and after open-heart surgery in a child with Glanzmann thrombasthenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…We have demonstrated that a large range of doses have been used, with positive results at lower doses (38,49). When rFVIIa was originally licensed for hemophilia patients, the standard recommended dose was 90 -120 g/kg every 2-3 hrs until bleeding stopped (71), and indeed, most of the studies in our review reporting on patients with congenital coagulopathies have used that regimen (40,44,51,60). However, it does not automatically extrapolate that this is the correct treatment for nonhemophiliac children who are post-surgery and "in extremis" with the resulting physiologic disturbance this brings.…”
Section: Discussionmentioning
confidence: 90%
“…We have demonstrated that a large range of doses have been used, with positive results at lower doses (38,49). When rFVIIa was originally licensed for hemophilia patients, the standard recommended dose was 90 -120 g/kg every 2-3 hrs until bleeding stopped (71), and indeed, most of the studies in our review reporting on patients with congenital coagulopathies have used that regimen (40,44,51,60). However, it does not automatically extrapolate that this is the correct treatment for nonhemophiliac children who are post-surgery and "in extremis" with the resulting physiologic disturbance this brings.…”
Section: Discussionmentioning
confidence: 90%
“…475 There are small, single-center experiences in pediatric patients with intractable hemorrhage after cardiac surgery, among patients with known factor deficiency or coagulopathy after cardiac surgery, and among patients placed on ECMO after cardiac surgery with intractable hemorrhage. [476][477][478][479][480][481][482][483][484][485] These studies suggest that recombinant FVIIa is effective in decreasing postoperative bleeding, but thrombotic complications have been reported, including an arterial thrombus in an infant requiring amputation of a leg. 484 The dose used among pediatric patients with intractable hemorrhage after cardiac surgery ranges from 30 to 180 μg/kg (recommended dose for patients with hemophilia, 90 μg/kg).…”
Section: Recombinant Fviiamentioning
confidence: 99%
“…A literature review revealed equal or less dosing of rFVIIa in comparison to our patient [3,4,7,9,[11][12][13]. The frequency of dosing intervals and the total duration of treatment should be individually adjusted, depending on the type of surgery and according to patient's clinical situation.…”
Section: Discussionmentioning
confidence: 98%
“…Severe bleeding complications are frequently seen after dental extractions, surgery, and childbirth. Nevertheless, only limited data are available on the management of patients with Glanzmann thrombasthenia undergoing major surgery [2][3][4]. Thus, the following is a report on the successful perioperative haemostatic management of a female patient with Glanzmann thrombasthenia who underwent elective abdominal hysterectomy.…”
Section: Introductionmentioning
confidence: 99%